PERSEDIAAN BAHAN BAKU PEMBUATAN BARECORE KAYU SENGON DI PT. SURYA SATRYA TIMUR CORPORATION BANJARMASIN - Fatih Farhan; Noor Mirad Sari; Gusti Akhmad Rahmad Thamrin (Universitas Lambung Mangkurat, 2020)
The purpose of this researchis to find the prediction of the use of raw materials the manufacture of barecore, determining the amount of reserving the raw material economical, knows when time reservation back and knew the amount of supplies safety at PT. Surya Satrya Timur Corporation Banjarmasin. The benefit of this research is to review and analyze and activity management production, especially in control supplies of raw materials. Barecore is layer of the core in process of making a blockboard which consist of a wood strip that arranged with such a manner. The raw materials is important for an industry, every industry need to do control activitiesas the raw materials supplies to make activities of production effective and efficient. Based on the result known that use of raw material in 2017 reached 3773,19 m³ withoptimum order as much as 38 times at 99,646 m³ every time order. The size of supply shall belong the corporate 49,50 m³ with a point reservation back whenraw materials reached 74,64 m³. the availability of raw material will be easing a process production of the economically and efficient. Keyword:Stock control; raw materials; barecore; EOQ